The Saga of Þórður kakali The Icelandic Text, with and English Translation by D.M. White - White, D.M (punctum books, 2020)
Icelandic literature, Nordic civil wars, saga, the Age of Sturlungar, thirteenth-century Iceland, Þórður kakali Sighvatsson